Adolescent obesity in contextual settings: a scoping study of multilevel and hierarchical examinations. Issue 5 (14th September 2016) - Utley, J. M.; Affuso, O.; Rucks, A. C.
Summary: Multilevel/hierarchical obesity studies analyze adolescent and family, neighbourhood and social settings' characteristics to generate data needed to design prevention interventions. This scoping study summarizes such studies' characteristics and key findings to provide information to decision makers, which allows them to quickly grasp the state of the evidence and potential policy implications for adolescent obesity prevention. PubMed, CINAHLplus, PsychINFO and Sociological Abstracts were searched for peer‐reviewed studies spanning 1 January 2000–31 August 2014. Inclusion criteria included (i) outcome weight status, physical activity and weight status, or physical activity alone if the aim was obesity prevention; (ii) 12‐ to 19‐year‐old participants in a cross‐sectional study, a separate analysis in a cross‐sectional study or a longitudinal follow‐up. Nineteen studies were published in the United States of America; four in Canada; two in Spain, China and Vietnam, respectively; and one in Germany. Self‐efficacy, parental physical activity support, perceived neighbourhood support, social cohesion and access to recreational facilities were associated with increased activity levels; neighbourhood physical disorder and perceived lack of safety associated with reduced physical activity levels. Overweight or obesity was associated with sugar‐sweetened beverage intake and household availability thereof; reduced odds were reported with fruit and vegetable intake and household availability of these, daily breakfast and family meal frequency. Potential adolescent obesity risk regulators may be found at the individual, family or social contextual levels.